Love of Money, Financial Literacy, Locus of Control dan Gender Terhadap Pengelolaan Keuangan Pribadi Pelaku UMKM - Aini, Khori Atul; Rahayu, Ruci Arizanda (Institut Bisnis dan Informatika Kesatuan, 2022)
This study was conducted to determine the effect of love of money, financial literacy, locus of control and gender on the personal financial management of SME actors. It belongs to quantitative research and the research sample is 35 SMEs in Wage village and its surroundings. The sampling technique applied is a saturated sample by making all members of the population as a sample, then distributing questionnaires through google form so that it gets 35 respondents. The purpose of sampling is saturated because the population used is relatively small. By using SPSS version 26, the data analysis techniques used include validity, reliability and multiple regression analysis. The results of this study state that there is no influence on the love of money variable on the personal financial management of SME actors. The financial literacy variable has a positive effect on the personal financial management of SME actors, which means that the better the literacy level of SME actors, the better in financial management behavior. The locus of control variable has a negative influence on the personal financial management of SME actors, which means that the higher the locus of control, the lower the financial management behavior. The gender variable has a positive influence on the personal financial management of SME actors, which means that the high understanding of gender roles can make the SME financial management better.